Brain Structure Alterations in Poly-Drug Use: Reduced Cortical Thickness and White Matter Impairments in Regions Associated With Affective, Cognitive, and Motor Functions - Unterrainer, Human F.; Hiebler-Ragger, Michaela; Koschutnig, Karl; Fuchshuber, Jürgen; Ragger, Klemens; Perchtold, Corinna M.; Papousek, Ilona; Weiss, Elisabeth M.; Fink, Andreas (Frontiers in Psychiatry, 2019)
Substance Use Disorders (SUD) are defined by obsessive and uncontrolled consumption, which is related to neurobiological changes. Based on previous work, this study investigated potential alterations in brain structure in Poly-drug Use Disordered (PUD) patients in comparison to controls from the normal population. This study involved a sample of 153 right-handed men aged between 18 and 41 years, comprising a clinical group of 78 PUD and a group of 75 healthy controls. Group differences in gray matter (GM) and white matter (WM), as well as cortical thickness (CT), were investigated by means of Diffusion Tensor Imaging (DTI) using Automated Fiber Quantification (AFQ) and Voxel-Based Morphometry (VBM). We observed significant WM impairments in PUD, especially in the bilateral corticospinal tracts and the inferior longitudinal fasciculi. Furthermore, we found reduced CT in the PUD group especially in the left insular and left lateral orbitofrontal cortex. There were no group differences in GM. In addition, PUD exhibited a higher amount of psychiatric symptoms (Brief Symptom Inventory) and impairments in cognitive functions (Wonderlic Personnel Test). In line with previous research, this study revealed substantial impairments in brain structure in the PUD group in areas linked with affective, cognitive and motor functions. We, therefore, hypothesize a neurologically informed treatment approach for SUD. Future studies should consequently explore a potential positive neuroplasticity in relation to a better therapeutic outcome.